2006
DOI: 10.1111/j.1741-3737.2006.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's Changing Attitudes Toward Divorce, 1974–2002: Evidence for an Educational Crossover

Abstract: This article examines trends in divorce attitudes of young adult women in the United States by educational attainment from 1974 to 2002. Women with 4‐year college degrees, who previously had the most permissive attitudes toward divorce, have become more restrictive in their attitudes toward divorce than high school graduates and women with some college education, whereas women with no high school diplomas have increasingly permissive attitudes toward divorce. We examine this educational crossover in divorce at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 20 publications
3
42
0
2
Order By: Relevance
“…First, a compositional effect may be operative, with countries with higher proportions of religious people having-on average-a more negative view on divorce in the presence of young children. Several studies have shown that religious beliefs and behaviour are associated with lower degrees of support for divorce (Thornton 1985(Thornton , 1989Larson and Goltz 1989;Krishnan 1994;Schovanec and Lee 2001;Martin and Parashar 2006). Second, there could be a contextual effect; in countries with a large proportion of religious people the Church may be more effective in propagating its teaching throughout society as a whole than in countries where a small minority of the people is religious.…”
Section: Country-level Determinantsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, a compositional effect may be operative, with countries with higher proportions of religious people having-on average-a more negative view on divorce in the presence of young children. Several studies have shown that religious beliefs and behaviour are associated with lower degrees of support for divorce (Thornton 1985(Thornton , 1989Larson and Goltz 1989;Krishnan 1994;Schovanec and Lee 2001;Martin and Parashar 2006). Second, there could be a contextual effect; in countries with a large proportion of religious people the Church may be more effective in propagating its teaching throughout society as a whole than in countries where a small minority of the people is religious.…”
Section: Country-level Determinantsmentioning
confidence: 99%
“…Thornton (1985) and Krishnan (1994) studied only women and also found a positive association between education and liberal views towards divorce. Yet, a trend study of divorce attitudes of young adult women in the United States between 1974 and 2002 gives evidence for an educational crossover: Women with 4-year college degrees, who previously had the most permissive attitudes towards divorce, have become more restrictive in their attitudes towards divorce than high school graduates and women with some college education, whereas women with no high school diplomas have increasingly permissive attitudes towards divorce (Martin and Parashar 2006).…”
Section: Individual-level Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside the sheer numerical increase of higher educated groups, that is, there has been a change in the attitudinal composition of these groups. In the US, for instance, the reported attitudes in favor of divorce decreased among highly educated and increased among lowly educated young adult women between 1970 and 2000 (Martin and Parashar 2006). Whether the economic status of educational groups has converged over the same time, however, is a more controversial question.…”
mentioning
confidence: 95%
“…However, Martin and Parashar (2006) note an "education crossover" in attitudes of younger women, ages 25 to 39, toward divorce. Between 1974 and 2002, women with bachelor's degrees, who previously had the most permissive attitude toward divorce, adopted a more restrictive attitude towards divorce than women with only some college did, while young women with no high school diploma adopted an increasingly permissive attitude.…”
Section: Direct Measures Of Attitudes and Normsmentioning
confidence: 99%